Pazopanib-Induced Cutaneous Leukocytoclastic Vasculitis: An Exclusion Diagnosis of a Multidisciplinary Approach - Diogo Alpuim Costa; Susana Baptista de Almeida; Pedro Coelho Barata; António Quintela; Pedro Cabral; Ana Afonso; João Maia Silva (Case Reports in Oncology, 2017)
In phase II/III trials, cutaneous side effects of pazopanib were reported in less than 20% of patients, with only 1–3% being grade 3/4. We present a case of a 66-year-old man with a previous history of left nephrectomy for a stage II clear cell renal carcinoma. Approximately 18 months later, recurrent disease in the lungs, mediastinum, and left psoas and bulky abdominal/pelvic nodal metastasis were documented. He was initially treated with pazopanib 800 mg q.d. and 1 week after starting this therapy, the patient presented with palpable purpura on his ankles. These lesions regressed within 2 weeks off pazopanib, but had recurred 4 weeks after he resumed medication at 400 mg q.d. Biopsy of the lesions revealed leukocytoclastic vasculitis. Despite tumour response to therapy, pazopanib was discontinued with total resolution of this skin toxicity within 2 weeks of his cutaneous toxicity. To the best of our knowledge, we report a rare yet significant cutaneous adverse reaction to pazopanib.